Children and autism - Ikonomi, Edison; Mema, Florian (Arena-Journal of Physical Activities, 2019)
Introduction. The development of children with autism involves the sphere of their activities and interests. They often have a limited range of activities and interests, express repeated behavior as well as various counteractions in the premises and everyday surroundings. Children with autism do not play the same way children with development normal. Their play lack imagination, they play by reproducing what they have seen or what they remember and do not add to their play parts from themselves, from their feelings and interpretation. Many children with autism express preferences for a definite object, a toy, a color, a certain shape, etc. Methodology The qualitative method was used in the study. Semi-structured interview with open-ended questions was the instrument for data collection. Data collections were made possible by interviewing of parents (10 parents) of children with ASD who were outpatients and inpatients at Centre Regional for Growth, Development and Rehabilitation Berat city. Results. Through data analyses it came out that: – Children with autism are limited in their activities, they play by copying and without imagination, show strong memory for what they want and express interest for certain definite objects, for toys musical, television, etc. – Children with autism are not focused in their daily activities and show behavior and actions that are stereotype and repetitive as for movement frequent of the hands, rotation of objects, etc. Conclusion. The development of children with autism involves the sphere of their activities and interests by limiting them.